Pemantauan dan Analisis Tingkat Pencemaran Kualitas Air Sungai di Kabupaten Tebo - Diana Sari; Nedy Yahya Nurhadi; Khairul Anwar; Muhammad Isa; Sri Handayani; Sardeni Sardeni (Universitas Hasanuddin, 2021)
Tebo regency has a very potential river as surface water to support human life. With the population growth in Tebo Tengah Districts and the development of its utilization, there is a tendency for changes occurred to the condition and quality of river. Density of the population can affect river environmental quality. This is happened because of awareness of the society in how to maintaining a healthy and clean environment. Estimation of water pollution can be done by looking at the influence of pollutants on the life of aquatic organisms and their environment. The units for estimating the presence of these pollutants are classified into biological, physical, and chemical parameters. In determining water quality, these parameters should not stand alone but it can show parameter itself and each of this has value which represents what is called the Water Quality Index. The purpose of this article is to know how the river water quality in Tebo Tengah Districts. This research used quantitative descriptive method. Quantitative method is utilized to determining the status quality of the water with vilification index method. Fecal, TSS, BOD5, DO and Total Phosphate values that exceed the quality standard indicate contamination from domestic and industrial wastewater. In addition, the occurrence of sedimentation due to land conversion causes the TSS value to exceed the quality standard. The calculation results for IKA value show that rivers in Tebo regency is in the lightly polluted category. That thing is because the behavior of the people who still throw garbage into the river environment, and the unavailability of public IPAL infrastructure to treat domestic waste water from residents' houses causes rivers in the Tebo Tengah Districts is still polluted.